Web design demystified - Willard, Wendy (McGraw-Hill "Demystified" series., 2011)
"Hard stuff made easy! Your practical, self-paced guide to Web designWeb Design Demystified covers all of the key concepts and technologies needed to master Web design fundamentals and become proficient in site design and implementation. Learn about the most common tools and best practices, as well as essential design features users expect. The book provides a basic understanding of HTML, XHTML, and CSS, which is the foundation for all Web design. This hands-on tutorial explains the basics of JavaScript, PHP, RSS and other necessary features for today's websites. Testing and verification, search engine optimization, FTP and other essentials of going live are also covered. Each chapter features hands-on exercise and a self-test to verify understanding. A comprehensive final exam covers all the core concepts presented in the book. Web Design Demystified shows how to use the essential technologies for current Web design, including HTML, CSS, JavaScript, and more Provides a complete standalone tutorial in Web design for which no prior experience is required outlines the key topics covered in Web design classes includes end-of-chapter quizzes and a final exam to reinforce learning and pinpoint weaknesses. Step-by-step coverage: getting started; designing for screens; building the pages; all about HTML; all about CSS; integrating HTML and CSS for layout; beyond HTML & CSS; Using Templates; Going Live; Email Design"-- Provided by publisher.